Current Problems in Provision of Orphan Drugs and Ways to Solve Them - Alexei S. Kolbin (Voprosy Sovremennoj Pediatrii, 2016)
Despite the fact that orphan (rare) diseases are characterized by a very low prevalence rate, a considerable number of people worldwide suffer from these diseases. The United States and the European Union developed a variety of economic and administrative incentives for pharmaceutical companies to produce orphan drugs, but their effectiveness is difficult to assess because of the small sample volume and complex organization of clinical trials. The average cost of orphan drugs is 5 times greater than that of the drugs used in the treatment of other diseases. Pricing mechanisms on orphan drugs are still poorly understood.